Chlorine dioxide gas treatment improves the quality of hardy kiwifruit (Actinidia arguta) during storage - Park, Hyowon; Han, Narae; Kim, Chul-Woo; Lee, Uk (Forest science and technology, 2019)
The effects of gaseous chlorine dioxide fumigation treatment on the quality of Actinidia arguta "Daebo," a hardy kiwifruit, were investigated. Hardy kiwifruit was fumigated with 30 mg L −1 chlorine dioxide gas for 30 min and stored at 2 °C for 5 weeks. Fruit firmness rapidly decreased the first 2 weeks of storage after fumigation, whereas the content of soluble solids increased. However, the firmness of chlorine dioxide-treated fruits was significantly higher than that of control fruits after 2 weeks of storage, indicating that the treatment helped to maintain the firmness of hardy kiwifruit. The changes in soluble solids content and titratable acidity during storage suggested that the ripening process of the hardy kiwifruit was delayed in gas-treated fruit. Moreover, chlorine dioxide gas treatment reduced the decay incidence and population of microorganisms on fruit surface. These results suggest that treatment with gaseous chlorine dioxide alleviates the deterioration of fruit quality in "Daebo" hardy kiwifruit during cold storage.